(untitled) (Cadernos do Laboratorio Xeolóxico de Laxe. Revista de Xeoloxía Galega e do Hercínico Peninsular, 2019)
Tanks (mega gnammas) of natural origin excavated in rock constitute medium-sized forms very frequent in the granite reliefs of Northeast Brazil. The study of the accumulated sediments inside these natural tanks has become a source of data of great interest for the knowledge of the quaternary paleontology of Brazil. This type of cavity in areas of granite substrate, once exposed on the surface have acted as local depocenters for water flows and associated sediments, sometimes fossiliferous, which has turned these hollows into true thanatocoenoses. The systematic study of the fossiliferous accumulations has become the main tool to reconstruct the paleoenvironmental and paleoecological conditions during part of the Quaternary period in the Brazilian Intertropical Region.